RANCANGAN PENGEMBANGAN PELABUHAN PERIKANAN PELABUHANRATU TERKAIT DENGAN PENINGKATAN KARAKTERISTIK KELAS PELABUHAN PERIKANAN DAN PEMILIHAN JENIS KAPAL PENANGKAP IKAN - Nur, Iswadi; Sudjasta, Bambang; Martana, Budhi (Bina Teknika, 2016)
Pelabuhanratu National Fishing Port can be changed to Pelabuhanratu Oceanic Fishing Port, but it should be proper to the class characteristic regulation of KKP, number 16, 2006. It has several condition, as ; the fishing vessel fleet have service area in the ZEE territorial and the International Ocean, the quay wall fasility > 60 GT, the port quay dimension has length > 300 m and deep of sea water > 3 m, amount of fish production 60 ton per day, the fishing port capacity > 6000 GT per day, it has the quality assurance facility of fish production, the area of fishing port > 30 hectares, it has the zone of fish processing industry. The result of research had many factors that had not been proper to the KKP regulation, as; amount of fish production = 25,030 ton per day, the fishing port capacity approximately 268,957 GT per day, the area of fishing port < 30 hectares, the zone of fish processing industry had not completed, so Pelabuhanratu National Fishing Port can not be changed to Pelabuhanratu Oceanic Fishing Port. Related to the fishing vessel that to be proper to the characteristic of its service area, as ; the capacity of fishing vessel up to 60 GT and minimum speed 12,5 knots, the fishing vessel has minimum 6 fish holds, the location of fish hold in the middle body, the fishing vessel hull has the bilge keel plate, and the material of hull fishing vessel to be made of wooden, steel, aluminium, or fiberglass.